Pengaruh Model PjBL Terhadap Hasil Belajar Siswa Kelas VIII pada Mata Pelajaran Bahasa Indonesia di MTs Muhammadiyah Padang Panjang - Lestari, Ayu Indra; Anugrah, Septriyan; Bentri, Alwen; Rahmi, Ulfia (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the influence of the project-based learning model on Indonesian subjects in grade VIII at MTS Muhammadiyah Padang Panjang. This research was carried out with a quantitative research method in the form of a Quasi Experiment. There were 70 students as a sample in class VIII consisting of 35 people in the experimental class and 35 people in the control class. The data collection technique used is a test at the beginning and at the end of Indonesian learning. The data analysis techniques are normality tests, homogeneity tests, and hypothesis tests with the t-test method. The results of the study show that the application of the Project Based Learning (PjBL) learning model has an effect on the learning outcomes of grade VIII students, as evidenced by the t-test value that has been carried out using Microsoft Excel in this study of 9.395 which is greater than the ttable 1.668 at the significance level of α 0.05, meaning that Ha is accepted and Ho is rejected. There is a significant difference between the average learning outcomes of students using the PjBL learning model. Therefore, it can be concluded that the application of the Project Based Learning model has an effect on student learning outcomes in Indonesian subject grade VIII MTS Kauman Muhammadiyah Padang Panjang